Credit risks and internationalization of SMEs - Arslan, Özgür; Karan, Mehmet Baha (Journal of Business Economics and Management, 2009)
The purpose of the paper is to identify common attributable factors causing credit risks to domestic and international SMEs of an emerging market in Turkey. We call domestic firms as the ones only making local sales and international firms as the ones also making sales abroad. Therefore in this study, cross‐border sales are assumed to lead the firms to internationalization. We study totally 1,166 SMEs for the year 2007, which coincide with an economic expansion in Turkey. We find that different factors affect credit risks for the two types of firms. For domestic firms, our results present a direct relationship between the likelihood of corporate default and trade credits, corporate tax, financial expenses and net profit margin yet the relationship turns negative for gross profit margin. For international firms, likelihood of corporate default increases with the ratio of inventories to total assets but decreases with net profits and net sales. First Publish Online: 14 Oct 2010